ANALISIS RASIO ARUS KAS UNTUK MENILAI KINERJA KEUANGAN PERUSAHAAN MANUFAKTUR SUB SEKTOR MAKANAN DAN MINUMAN YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2015-2019 - Meylinda Anggitasari; Yunita Niqrisah Dwi Pratiwi; Alean Kistiani Hegy Suryana (Universitas Boyolali, 2023)
Financial performance is an analysis to assess the extent to which the company has carried out activities based on good financial implementation rules. The purpose of this study was to determine the financial performance of the food and beverage sub-sector manufacturing companies listed on the Indonesia Stock Exchange for the 2015-2019 period. The results showed that the value of the ratio in the company fluctuated and it can be concluded that the financial performance of the food and beverage sub-sector companies from the aspect of the operating cash flow ratio, cash coverage ratio to interest, capital expenditure ratio, cash flow ratio to net profit, and total debt ratio , it is known that the food and beverage sub-sector manufacturing companies for the 2015-2019 period experienced fluctuations. Financial performance in good condition at ADES (Akasha Wira Internasional Tbk), CEKA (PT.Wilmar Cahaya Indonesia Tbk), and AISA (FKS Food Sejahtera Tbk) companies.